Modificação do método de avaliação dos estágios maturacionais da sutura palatina mediana - Piccoli, Vicente Dias (2018)
Introduction: The present study proposed a redefinition of the maturational stages of the midpalatal suture (MPS) through reassessment of the intermediate stages B, C and D. Methods: A total of 158 cone-beam computed tomography (CBCT) scans of individuals between 11 and 20 years (average 15.4 years) were analyzed, comprising 86 females and 71 males, including stages previously classified as B (29), C (92) and D (37), divided in 74 individuals aging 11-15 years and 84 individuals aging 16-20 years. Each axial image was subdivided into 6 parts in anteroposterior direction, and each part classified and recorded according to the MPS maturational evaluation method. A new definition of stages was elaborated. The reliability of the method was tested by two examiners and intra and inter-examiner agreement were defined in the two evaluations through the weighted kappa coefficient, adopting a 95% confidence interval. Results: Two new maturational stages were defined: sub-stage C- and sub-stage C+, with a prevalence of 12% and 8.9%, respectively, in 11-20 years individuals. Conclusion: The redefinition and validation of the maturational stages of MPS, allows us to elucidate the difference in the prognosis of rapid maxillary expansion among individuals aged 11-20 years, which should be investigated through a clinical study.